Mechanistic QSAR models for interpreting degradation rates of sulfonamides in UV-photocatalysis systems. (November 2015) - Huang, Xiangfeng; Feng, Yi; Hu, Cui; Xiao, Xiaoyu; Yu, Daliang; Zou, Xiaoming
Highlights: Substituent groups have a substantial impact on the degradation efficiency of SAs. Mechanistic models were developed to interpreting degradation rates of SAs. Degradation relate to quantum chemical descriptors and adsorption features. Abstract: Photocatalysis is one of the most effective methods for treating antibiotic wastewater. Thus, it is of great significance to determine the relationship between degradation rates and structural characteristics of antibiotics in photocatalysis processes. In the present study, the photocatalytic degradation characteristics of 10 sulfonamides (SAs) were studied using two photocatalytic systems composed of nanophase titanium dioxide ( n TiO2 ) plus ultraviolet (UV) and n TiO2 /activated carbon fiber (ACF) plus UV. The results indicated that the largest apparent SA degradation rate constant ( Kapp ) is approximately 5 times as large as that of the smallest one. Based on the degradation mechanism and the partial least squares regression (PLS) method, optimum Quantitative Structure Activity Relationship (QSAR) models were developed for the two systems. Mechanistic models indicated that the degradation rule of SAs in the TiO2 systems strongly relates to their highest occupied molecular orbital ( Ehomo ), the maximum values of nucleophilic attack ( f (+) x ), and the minimum values of the most negative partial charge on a main-chain atom ( q (C)min ), whereas the maximum values of OH radical attack ( f (0) x ) and the apparent adsorption rate constant values ( kad ) are key factors affecting the degradation rule of SAs in the TiO2 /ACF system.